Does ethnicity matter in individual taxpayer's compliance behaviour?: Empirical evidence from Nigeria - Alabede, James O. (Global Research Society, 2011)
A number of factors may be responsible for low compliance behaviour among the individual taxpayers in Nigeria.This study incorporates ethnicity into the tax compliance model for better understanding of the phenomenon and it determines whether multi-ethnic background of the taxpayers causes a significant difference in compliance behaviour in a highly ethnic fractionalized and polarized society as Nigeria.The data of the study were collected through the survey of Nigerian individual taxpayers and the data were statistically treated using multiple regression analysis.The study provides evidence that indicates race as a determinant of tax compliance behaviour in a highly ethnic fractionalized and polarized society.